Liver kinase B1 attenuates liver ischemia/reperfusion injury via inhibiting the NLRP3 inflammasome. (30th March 2021) - Dai, Jiangwen; Chen, Qingsong; Huang, Weifeng; Shi, Kun; Zhang, Yuke; Li, Tingting; Mou, Tong; Huang, Zuotian; Wu, Zhongjun
Abstract: Liver ischemia/reperfusion injury (IRI), a serious inflammatory response driven by innate immunity, occurs in liver surgeries such as liver resection and liver transplantation, leading to liver dysfunction, liver failure, and even rejection after transplantation. Liver kinase B1 (LKB1) plays a pivotal anti-inflammatory role in IRI. One of the most important factors involved in liver IRI is the aberrant activation of the nucleotide binding oligomerization domain like receptor (NLR) family, pyrin domain-containing 3 (NLRP3) inflammasome in Kupffer cells. However, the mechanisms underlying the effect of LKB1 on the NLRP3 inflammasome in liver IRI remain elusive. In this study, we found that the expression of LKB1 was decreased in liver IRI, while the NLRP3 inflammasome level was increased as shown, as revealed by RT-qPCR and western blot analysis. Furthermore, upregulation of LKB1 abrogated the expression of the NLRP3 inflammasome, which improved liver function and liver pathology in the liver IRI model in vivo. In vitro, overexpression of LKB1 inhibited the activation of NLRP3 inflammasome and nuclear factor-κB, while the inhibitory effect was reversed by silencing the expression of the forkhead box protein O1 in the RAW264.7 macrophage hypoxia/reoxygenation model. In conclusion, our results suggest that LKB1 exerts a protective effect against liver IRI by downregulating the NLRP3 inflammasome.